Model of Institutional Integration of the Community Revolving Fund as a Source of Sustainable Capital and Poverty Alleviation in Rural Areas - Emi Hidayati; Akhmad Sofyan; Djoko Poernomo; Supranoto (GoAcademica Research & Publishing, 2023)
This study attempts to create an integration model of institutional change from a government-driven initiative, specifically the integration of community revolving funds (DBM) into Village-Owned Enterprises (BUMDesa). In particular, every village in Banyuwangi Regency having a Village Credit Bank was included in this study. This study used descriptive qualitative research. The information was gathered using a combination of in-depth interviews, participant and non-participant observation, and document reviews. The data was examined for validity using a series of source triangulation, technique triangulation, and time triangulation. The institutional dynamics of community revolving funds (DBM) arising from government policies or programs. It was governed by overlapping rules from different independent bodies, which made it challenging to implement the transformation process and expensive to do so. The Village Credit Bank and the PNPM-Mandiri activity implementation unit (UPK) were eventually merged to create the Bumdesma business unit after overcoming numerous challenges. The Inter-Village Cooperation Agency (BKAD) and Bumdesma are two new organizations that were created as a result of the institutional change process but their existence does not enhance community services. The dynamics of institutional change and transformation led to disagreements over property rights, and uncertainty surrounding ownership status sparked the emergence of Free Riders who later converted BKD assets into KSPs run by a number of former managers, which in turn had an impact on the sale of BKD assets to private parties. The institutional transformation process caused BKD's institutional nature to move from private goods to common goods as a secondary bank of BRI. The oversight of Microfinance ex Village Credit Bank (BKD) is the sole aspect of Bumdesa business units that are covered in this research. This research is able to contribute a model of integrating the management of Bumdesa as a Common Resource as an effort to alleviate poverty in Indonesia.